Варіанти способів внутрішньої ємнісної компенсації реактивної потужності асинхронних двигунів - Чуєнко, Р. М. (Energy and Automation, 2017)
VARIATIONS OF INDUCTION MOTOR’S REACTIVE POWER INTERNAL CAPACITANCE COMPENSATIONChuenko RomanWays of induction motors power efficiency improvement using internal capacitance compensation are analysed.Key words: Compensated induction motor, power efficiency, reactive power, stator winding, autotransformerSquirrel-cage induction motor is the most widespread mean of transformation  electric energy into mechanical in the agricultural working machines.From literature the different going is known near the decision of problem of increase induction electric motor’s efficiency. In particular, asynchronous electric motors the power indexes of that rise due to the increase of weight parameters and improvement of quality of active materials are created. Deserves attention experience of power increasing descriptions of asynchronous motors due to the use of special construction stator winding with connecting of condensers of electric capacity. However for these motors characteristic is relatively a heavy toll of active materials on unit of useful power and weight parameters, in addition due to more complicated  technological process of stator winding making of these motors substantially increases their cost.Realization of internal capacitance reactive power compensation in induction motors can be carried out in number of different ways in dependence on the accepted chart and amount of parallel branches of base machine stator winding. Taken into account thus, that in accordance with the pair amount of poles the stator winding always can be divided into two identical consistently or multipled parts (semiwindings). However for small machines (with power to 11 kW) more effective is successive connection of semiwindings, and more powerful machines must have stator windings connected in parallel.The first method of internal capacitance reactive power compensation in induction motors consists in that at successive connection of stator semiwindings one of them is shunted by the condenser of electric capacity. Thus shunted semiwinding interchanges a reactive-power not with the network of feed, but with a condenser. As a result unshunted phase stator semiwinding of the compensated of compensated induction motor partly or fully rids of transmission of reactive-power to the shunted semiwinding, and it’s current reduces.It is suggested to use another method of internal capacitance reactive power compensation in induction motors. In this occasion phase stator winding consists of basic semiwinding and additional semiwinding, displaced in slots of stator on the autotransformer circuit to electric capacity. Thus stator windings of compensated induction motor are functionally combined, as working motor’s windings and compensated windings for reactive-power.Compensated induction motor is guided on the reactive power volume and character of power transformations that flows in it. The power, mechanical and efficiency indexes of compensated induction motor depend on the angle of spatial change between the axes of basic and compensative stator windings, size and chart of connection of compensating capacities.The most favorable mode of operations of compensated induction motor is observed at the angles of spatial displacement of stator semiwindings ±30о. The fundamental condition of internal capacitance reactive power compensation in induction motors is providing of such spatio-temporal change of currents of basic and additional stator windings, that doubling of amount of phases took place at unchanging three-phase voltage.